Sociālā pedagoga darbība pirmsskolas izglītības iestādē bērnu labizjūtas sekmēšanā. - Karple, Kristīne (Latvijas Universitāte, 2022)
Kristīne Karples diplomdarbs “Sociālā pedagoga darbība pirmsskolas izglītības iestādē bērnu labizjūtas sekmēšanā” izstrādāts ar mērķi izpētīt sociālā pedagoga darbību bērnu labizjūtas sekmēšanā pirmsskolas izglītības iestādē. Teorētiskajā daļā tiek raksturota pirmsskolas izglītības iestāde, bērnu labizjūtas sekmēšana pirmsskolas izglītības iestādē, adaptācijas procesa un labizjūtas savstarpējā saikne, sociālā pedagoga funkcijas bērnu labizjūtas sekmēšanā. Praktiskajā daļā tiek veikts pētījums par sociālā pedagoga darbību pirmsskolas izglītības iestādē bērnu labizjūtas sekmēšanā un izstrādāta sociālpedagogiskā darbības programma par labizjūtas sekmēšanu pirmsskolas izglītības iestādē, kas aprobēta un izvērtēta. Atslēgvārdi:labizjūtas sekmēšana, sociālais pedagogs, adaptācija, pirmsskolas izglītības iestāde, sociālpedagoģiskā darbības programma.

Kristīne Karples' thesis “Activities of a social pedagogue in a pre-school educational institution in promoting the well-being of children” was developed with the aim to study the activities of a social pedagogue in promoting children s well-being in a pre-school educational institution. The theoretical part describs the pre-school educational institution, the promotion of children's well-being in the pre-school educational institution, the interrelation of the adaptation process and well-being, the functions of a social pedagogue in promoting children's well-being. In the practical part, a research on the activities of a social pedagogue in a pre-school educational institution in promoting the well-being of children was carried out . The socio-pedagogical action program on the promotion of well-being in a pre-school educational institution was developed. Approbation of the social pedagogical activity program and analysis of the obtained results were performed. Keywords: well-being promotion, social pedagogue, adaptation, pre-school educational institution, social pedagogical action program.
Activities of social teachers in pre-school education institutions in promoting the well-being of children.
Keywords: Pedagoģija; labizjūtas sekmēšana; sociālais pedagogs; adaptācija; pirmsskolas izglītības iestāde; sociālpedagoģiskā darbības programma